2022
DOI: 10.5089/9798400200960.087
|View full text |Cite
|
Sign up to set email alerts
|

European Labor Markets and the COVID-19 Pandemic: Fallout and the Path Ahead

Abstract: AcknowledgmentsThis departmental paper was led by Ravi Balakrishnan and Nir Klein, under the overall guidance of Jörg Decressin. It has benefited immensely from review and comments by many IMF staff colleagues in the European, Fiscal Affairs, Strategy Policy and Review, and Research Departments. We gained many insights from participants at numerous presentations of this work, including at the European Commission, the European Central Bank, and several national authorities in the context of Article IV Consultat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…While the labour market of the developed nations recovered quickly from the COVID-19 pandemic, now we are facing labour shortages all around the world. This picture is mostly influenced by cyclical considerations, as workers are more prone to switch jobs in the hope of finding better employment during times of tight labour markets (Causa et al, 2022;Ando et al, 2022;Navickas et al, 2022). According to Astorquiza Bustos et al (2022), the most influencing structural changes were obvious for young people and in the artistic activities sector.…”
Section: The Impact Of the Pandemic And War On The Labour Marketmentioning
confidence: 99%
“…While the labour market of the developed nations recovered quickly from the COVID-19 pandemic, now we are facing labour shortages all around the world. This picture is mostly influenced by cyclical considerations, as workers are more prone to switch jobs in the hope of finding better employment during times of tight labour markets (Causa et al, 2022;Ando et al, 2022;Navickas et al, 2022). According to Astorquiza Bustos et al (2022), the most influencing structural changes were obvious for young people and in the artistic activities sector.…”
Section: The Impact Of the Pandemic And War On The Labour Marketmentioning
confidence: 99%
“…Hypothesis 2-Impact of a decrease of the absolute advantage of the unskilled labor in production Several studies have examined the impact of the pandemic on various aspects of the labor market, including the productivity of unskilled workers. Ando et al (2022), Mongey et al (2021), and OECD (2020), among others, have reported that the productivity of unskilled workers was especially affected by the pandemic. Despite the potential for remote work, many unskilled workers were unable to make the transition, resulting in a significant decrease in their productivity.…”
Section: 22mentioning
confidence: 99%
“…In addition to the impact on labor supply, several studies have explored how the pandemic has impacted the labor productivity. Ando et al (2022), Mongey et al (2021), and OECD (2020) have all reported that unskilled workers' productivity was significantly affected by the pandemic. While some of these workers could transition to remote work, many lacked the necessary skills, resulting in decreased productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed since the onset of the pandemic, several countries have observed movements in their Beveridge curves. From Germany, Spain and UK (Ando et al, 2022) to Denmark (Darougheh, 2022) and Ireland (An Roinn Airgeadais, 2021), economists have reported outward shifts in their countries' Beveridge curves. In the US in particular, multiple researchers (Blanchard, Domash and Summers, 2022; Rodgers and Kassens 3 , 2022; Bok et al, 2022;Figura and Waller, 2022) have identified a significant rightward Beveridgean shift since the pandemic hit.…”
Section: Introductionmentioning
confidence: 99%